Nurses' Quality of Performance in Intensive Care Units based on Synergy Model - M Karimyar Jahromi (Iran University of Medical Sciences, 2013)
Abstract   Background and Aims: Quality of services and products has always attracted people. Synergy model provides a unified framework to describe nursing job, peer review functionality, quality of performance improvement and the care pathway. This study aimed to determine the intensive care unit nurses' quality of performance in Shiraz and Jahrom according to Synergy model.   Material ;Methods: It was a descriptive study. The nurses working in ICUs were recruited by census (n=364) in 2012. The checklist of quality performance was constructed according to Synergy model concepts and was completed by nurses. Total performance score and the scores of different dimensions were calculated. Data was analyzed by chi-square test t- test and Wilcoxon test using SPSS-PC (v. 16).   Results: The results show that the nurses have expressed their best performance in the areas of collaboration (99.1± 6.02) and caring practice (97.92± 3.6) and their lowest performance in the areas of clinical inquiry (81.98± 4.7) and response to diversity (85.98± 3.8). Also additional findings revealed that there were statistically significant differences between Shiraz and Jahrom nurses' performance in the areas of clinical judgment, collaboration, system thinking, response to diversity, and learning facilitation and overall performance (p value <0.05).   Conclusion : Regarding the capabilities of Synergy Model in determining the required standards to empower ICU nurses, it can improve the quality of health care team performance, especially nurses and thus improve the care outcomes, prognosis and satisfaction of patients in ICUs.  Received: 11 March 2013   Accepted: 12 Jun 2013